Design Aspects of Printed Monopole Antennas for Ultra-Wide Band Applications. (7th April 2008) - Ray, K. P.
Abstract : This paper presents the design equations for lower band-edge frequency for all the regular shapes of printed monopole antennas with various feed positions. The length of the feed transmission line is a critical design parameter of these monopole antennas. Design curves for the length of the feed transmission line for various lower band-edge frequencies for all these regular shaped monopoles have been generated. A systematic study has been presented to explain the ultra-wide bandwidth obtained from these antennas with an example of elliptical monopole antenna.